I can work out what the expression simplifies to and can show the equivalence with a truth table, but I don't know the law (or sequence of laws) that need to be applied to show this formally.
This is the expression:
¬X OR (Y AND X) where ¬ is NOT.
and it simplifies to:
¬X OR Y
WolframAlpha also shows this when expressing it in CNF:
This is part of a homework question and just need help understanding how this stage works. I've read through the laws and searched the Internet and any law I try to apply doesn't produce the correct expression.